PERALIHAN HAK ATAS TANAH MELALUI PERJANJIAN PENGIKATAN JUAL BELI (PPJB): BATAS PERLINDUNGAN PEMBELI BERITIKAD BAIK - Ardhian Lukman Hakim; Dara Puspita (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study clarifies the legal status of the Preliminary Sale and Purchase Agreement (PPJB) within Indonesia’s land transfer framework and delineates the limits of legal protection for good-faith purchasers at the pre-levering stage. The central issue lies in the tension between PPJB’s obligational nature and the publicity principle of land registration, particularly when confronted with third parties who have lawfully acquired a Deed of Sale and Purchase (AJB) and registered their rights. Employing a normative legal method, this research applies a statute approach (UUPA, Government Regulation 24/1997 as amended by 18/2021, Condominium Law, and relevant PUPR regulations), a conceptual approach (subjective–objective good faith, pacta sunt servanda, publicity), and a case approach (judicial tendencies). The findings demonstrate that PPJB creates only a personal claim and does not transfer real rights prior to AJB execution and registration. The “good-faith purchaser” status requires measurable, documented, and provable due diligence. Priority attaches to registered rights held by good-faith third parties, rendering PPJB purchasers’ protection primarily remedial. This study proposes an operational Good-Faith Test Matrix (Minimum Due Diligence) to support objective assessment and dispute prevention.